The Prophetic Speeches (Hadith) on Sciences and Scientists: Application of the "Text from Text and D+" Theory (Journal of the College of Education for Women, 2023)
This study aims to apply the theory of "Text from Text and the Plus Dimension" in the analysis of the Prophetic discourse found in the section on the virtues of knowledge and scholars from Imam Sahih al-Bukhari's book. This section covers several topics, including the virtue of gathering for the sake of learning, the superiority of a scholar over a worshipper, the excellence of jurisprudence in the religion of Allah, the acquisition of knowledge through the passing away of scholars, the merit of inviting people to Allah, the continuing benefit of beneficial knowledge after a scholar's demise, the warning against seeking knowledge for purposes other than Allah, and the Prophet seeking refuge from knowledge that brings no benefit. This is an applied analytical study that aims to elucidate the scientific miraculousness in the Prophetic hadiths and explain the meanings of the Prophetic sayings in harmony with scholars and the majority. It also seeks to derive moral lessons from the hadiths and reveal meanings that might be ambiguous or hidden using the "Text from Text and the Plus Dimension" theory in the analysis of the Prophetic discourse. The study arranges the sentences of the hadiths in the section on the virtues of knowledge and scholars from Sahih al-Bukhari's book and examines their meaning and rhetorical composition. It links them with mathematical geometric relationships such as rotation, expansion through magnification and contraction, withdrawal (beginning with the beginning), and reflection (beginning with the end). The study adopts an analytical and explanatory methodology to achieve its objectives, and the corpus of the study consists of Prophetic hadiths from the section on the virtues of knowledge and scholars from Sahih al-Bukhari's book, along with all its topics. This research builds upon two previous studies where the theory was applied to analyze the Prophetic discourse: "Inviting to Contemplate the Prophetic Discourse: Text from Text and the Extra Dimension in the Analysis of the Prophetic Discourse" (Al-Rawajfeh, 2020) and "The Theory of Text from Text and the Extra Dimension in the Analysis and Miraculousness of the Prophetic Discourse: An Application to the Book of Faith from Sahih al-Bukhari" (Al-Rawajfeh and Al-Jubbah, 2023)